The Relationship Between Stress Levels And Physical Activity On The Physical Fitness Level Of Students At SMA Negeri 1 Talang Padang, Tanggamus Regency - Ismawati, Septiyani; Heru Sulistianta; Joan Siswoyo; Lungit Wicaksono (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
This study aims to determine the relationship between stress levels and physical activity on the physical fitness level of high school students. The population in this study consists of students from grades X, XI, and XII at SMAN 1 Talang Padang, with a randomly selected sample of 96 students. The research method used is a quantitative descriptive method with a correlational approach. The instruments used for data collection include the Perceived Stress Scale Questionnaire (PSSQ), the Physical Activity Questionnaire for Adolescents (PAQ-A), and the Indonesian Student Fitness Test (TKSI). For data analysis, the researcher utilizes SPSS 25. The results of the study show a significant relationship between stress levels and physical activity on physical fitness, as indicated by a Sig. F Change value of 0.000 < 0.05, with an R value of 0.838. From this output, the coefficient of determination (R square) is 0.702, indicating a strong correlation. It can be concluded that stress levels and physical activity have a strong relationship with physical fitness.